Impact of Wearable Technology on Enhancing Backhand Stroke Performance in Tennis among Physical Education and Sports Science Students at the University of Baghdad - Waheeb, Ali Abdulsalam (Journal of Physical Education, 2025)
This research aimed to investigate the impact of Using wearable technology for improving backhand stroke among students of Physical Education and Sports Science, in University of Baghdad. It aimed at assessing better performance with respect to stroke accuracy, feeling and reduction of vibrations, as well as being capable to provide real-time feedback on the student's quality of movement with wearable sensors. An experiment designed conducted with the sample 24 novice students (12 experimental, 12 control) during intervention period of 8 weeks. The experimental group received real-time biomechanical feedback using wearable sensors, whereas the control group underwent conventional training. Accuracy, speed and vibration were evaluated by pre- and post-testing of a standard backhand stroke protocol. Data were statistically examined through SPSS and outcomes were compared by t-tests and ANOVA. Results: The experimental group had significantly better results in backhand accuracy, speed and vibration reduction compared to the control group (p < 0.05). ANOVA revealed significant interaction effects, a difference that only wearable technology is able to make. Conclusions Wearable technology significantly improves performance of the backhand stroke, minimizes the risk of injury, and enables effective skill acquisition. Its inclusion in the sports education curriculum is recommended to improve training results where resources are limited.